2020
DOI: 10.11646/phytotaxa.440.2.3
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Description of <em>Stenomitos kolaenensis </em>and <em>S. hiloensis sp. nov. </em>(Leptolyngbyaceae, Cyanobacteria) with an emendation of the genus</strong></p>

Abstract: Stenomitos is a recently established cyanobacterial genus, some species of which appear to be cryptic. Here we describe two new species in this genus, Stenomitos kolaensis sp. nov. isolated from the Al-Fe humic podzols of a boreal forest near Nikel town, Murmansk region, Russia and S. hiloensis sp. nov. isolated from a basaltic seep wall on Akeola Road, Hilo, Hawaii, USA. Phylogenetic analyses were conducted on the 16S and 16S-23S ITS rRNA gene regions using Bayesian Inference, and Maximum Likelihood. Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 1 publication
1
46
0
Order By: Relevance
“…4b10 (Swofford 1998). For this analysis, indels were counted as a fifth base following standard phylogenetic methods for cyanobacterial ITS sequence data (Perkerson et al 2011, Osorio-Santos et al 2014, Bohunick a et al 2015, Mare s et al 2019, Becerra-Absal on et al 2020, Mesfin et al 2020, Shalygin et al 2020. A total of 10,000 bootstrap replicates were obtained for this analysis.…”
Section: Sample Collectionmentioning
confidence: 99%
“…4b10 (Swofford 1998). For this analysis, indels were counted as a fifth base following standard phylogenetic methods for cyanobacterial ITS sequence data (Perkerson et al 2011, Osorio-Santos et al 2014, Bohunick a et al 2015, Mare s et al 2019, Becerra-Absal on et al 2020, Mesfin et al 2020, Shalygin et al 2020. A total of 10,000 bootstrap replicates were obtained for this analysis.…”
Section: Sample Collectionmentioning
confidence: 99%
“…frigidus (Fig. 2) (Shalygin et al, 2020). These strains are likely to belong to newly reported genus Stenomitos isolated from cave habitats on Kauai, Hawaii (Miscoe et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It has been applied for the construction of phylogenetic trees and through the analysis of secondary structures of 16S-23S ITS regions (Johansen et al, 2011). Numerous studies confirmed the integrated approach of analyzing 16S rRNA gene phylogeny and 16S-23S ITS secondary structure to be useful and robust for complex cyanobacterial taxonomy, as in the case of the species or genera within the family Leptolyngbyaceae (Komarek et al, 2014;Debnath et al, 2017;Shalygin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…was proposed to a new genus as Enugrolinea bermudensis (Walter et al 2017), while L. frigida UCL18 appeared to be affiliated with a newly reported genus Stenomitos (Shalygin et al 2020).…”
Section: Phylogenetic Relationship Of Leptolyngbya Strainsmentioning
confidence: 99%